Gestão de segurança do trabalho na construção civil: a manutenção predial em uma indústria de alimentos - Makishima, José Narumi de Queiroz (2011)
Organizations have transferred to specialized companies that originally held the jobs of their employees with effective frameworks. This phenomenon has caused a growing movement known as outsourcing services. The outsourced companies have been established so fragile from the standpoint of safety at work, neglecting the most basic aspects established by the legislation, technical standards and best practice in this area in order to offer more economic proposals to deal with a market every increasingly competitive. It was established as a goal for this research to identify the practices adopted in terms of safety by a multinational company in the food industry field that is certified under OHSAS 18.001:2007, regarding outside contractors who provide building maintenance services with focus on civil construction activities during July 2009 thru June 2010. The methodology consisted of a detailed study relating to the contracting organization management system concerning outside contractors as well as of the records of accidents and preventive measures adopted to meet the requirements stipulated by the contractor. As a main result of this research it was identified that among the measures adopted, it were highlighted the establishment of administrative and technical procedures, such as the operationalization of key actions like work oriented on the requirements of OHSAS 18001, training programs, the legislation attendance, the definition of administration procedures and for risk management activities, a good relationship between the contractor and subcontractors, the organization of safety professionals, emergency preparedness and medical care. As conclusion it was found that the measures implemented were effective because they contributed to the branch of building maintenance with a focus on civil construction on presenting the best performance in terms of accident rates. Therefore it is recommended to consider the application of the preventive actions identified in this survey due to its effectiveness, and for the fact that the deployment process is basically administrative.